PARENTS 2 study protocol: pilot of Parents' Active Role and ENgagement in the review of Their Stillbirth/perinatal death. Issue 1 (10th January 2018) - Bakhbakhi, Danya; Siassakos, Dimitrios; Storey, Claire; Heazell, Alexander; Lynch, Mary; Timlin, Laura; Burden, Christy
Abstract : Background: The perinatal mortality review meeting that takes place within the hospital following a stillbirth or neonatal death enables clinicians to learn vital lessons to improve care for women and their families for the future. Recent evidence suggests that parents are unaware that a formal review following the death of their baby takes place. Many would welcome the opportunity to feedback into the meeting itself. Parental involvement in the perinatal mortality review meeting has the potential to improve patient satisfaction, drive improvements in patient safety and promote an open culture within healthcare. Yet evidence on the feasibility of involving bereaved parents in the review process is lacking. This paper describes the protocol for the Parents' Active Role and Engangement iN the review of their Stillbirth/perinatal death study (PARENTS 2), whereby healthcare professionals' and stakeholders' perceptions of parental involvement will be investigated, and parental involvement in the perinatal mortality review will be piloted and evaluated at two hospitals. Methods and analysis: We will investigate perceptions of parental involvement in the perinatal mortality review process by conducting four focus groups. A three-round modified Delphi technique will be employed to gain a consensus on principles of parental involvement in the perinatal mortality review process. We will use three sequential rounds, including a national consensus meeting workshop with experts in stillbirth, neonatal death and bereavement care, and a two-stage anonymous online questionnaire. We will pilot a new perinatal mortality review process with parental involvement over a 6-month study period. The impact of the new process will be evaluated by assessing parents' experiences of their care and parents' and staff perceptions of their involvement in the process by conducting further focus groups and using a Parent Generated Index questionnaire. Ethics and dissemination: This study has ethical approval from the UK Health Research Authority. We will disseminate the findings through national and international conferences and international peer-reviewed journals.